2006
DOI: 10.1523/jneurosci.2651-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Telencephalin Slows Spine Maturation

Abstract: Dendritic filopodia are highly dynamic structures, and morphological maturation from dendritic filopodia to spines is intimately associated with the stabilization and strengthening of synapses during development. Here, we report that telencephalin (TLCN), a cell adhesion molecule belonging to the Ig superfamily, is a negative regulator of spine maturation. Using cultured hippocampal neurons, we examined detailed localization and functions of TLCN in spine development and synaptogenesis. At early stages of syna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
105
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(114 citation statements)
references
References 60 publications
9
105
0
Order By: Relevance
“…Ontogenic appearance of TLCN parallels the timing of dendritic outgrowth, spine formation, and synaptogenesis in early postnatal life, and the expression persists into adulthood (Mori et al, 1987;. Recently, we reported that TLCN facilitates the formation and maintenance of dendritic filopodia and thereby slows spine maturation in hippocampal neurons (Matsuno et al, 2006). This function of TLCN requires both its extracellular and cytoplasmic regions, suggesting the involvement of unknown ligands/counter-receptors and cytoskeleton-associated intracellular binding partners in TLCN-mediated morphogenesis of dendritic filopodia.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Ontogenic appearance of TLCN parallels the timing of dendritic outgrowth, spine formation, and synaptogenesis in early postnatal life, and the expression persists into adulthood (Mori et al, 1987;. Recently, we reported that TLCN facilitates the formation and maintenance of dendritic filopodia and thereby slows spine maturation in hippocampal neurons (Matsuno et al, 2006). This function of TLCN requires both its extracellular and cytoplasmic regions, suggesting the involvement of unknown ligands/counter-receptors and cytoskeleton-associated intracellular binding partners in TLCN-mediated morphogenesis of dendritic filopodia.…”
Section: Introductionmentioning
confidence: 89%
“…Primary antibodies used in this study were as follows: guinea pig anti-mouse TLCN/Fc (1:1000) (Matsuno et al, 2006); rabbit antiphospho-ERM (1:100; Cell Signaling Technology, Beverly, MA); mouse anti-␣-actinin and mouse anti-FLAG M2 (1:400 and 1:10000, respectively; Sigma, St. Louis, MO); and rat anti-green fluorescent protein (GFP) (1:1000; Nacalai Tesque, Kyoto, Japan). Cyanine 3 (Cy3)-and Cy5-conjugated secondary antibodies were purchased from Jackson ImmunoResearch (West Grove, PA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fragile X syndrome, a common form of mental retardation, exhibits a higher than normal density of spines but more of them exhibit an immature morphology and their turnover is not affected by sensory experience (9,20). Conversely, the protein Telencephalin arrests the maturation of spines and its removal enhances several forms of learning (13,21,22).Although many molecules have been identified that affect synapse number, it is unclear how newly formed spines mature into synapses (13,23,24). On a cellular level, learning and memory are associated with long-term potentiation (LTP) and long-term depression (LTD) of neurotransmission.…”
mentioning
confidence: 99%
“…Fragile X syndrome, a common form of mental retardation, exhibits a higher than normal density of spines but more of them exhibit an immature morphology and their turnover is not affected by sensory experience (9,20). Conversely, the protein Telencephalin arrests the maturation of spines and its removal enhances several forms of learning (13,21,22).…”
mentioning
confidence: 99%